APLIKASI SISTEM INFORMASI DAFTAR NOMINATIF PERJALANAN DINAS ONLINE BERBASIS WEB (Studi Kasus Pusdiklat BMKG) - Saiful, Deni (Pusdiklat BMKG, 2020)
The nominative list is mandatory for business trip of a civil servant and required by the State financial managers. So far, the nominative list was simply made using Microsoft Excel and manually submitted. This generate a problem since the data are not saved in one folder so that making difficulty whenever they are needed. This situation led to an initiative to make an information system application to enable financial officers get access to the nominative list anywhere at any time as long as the internet access is available. The current work was undertaken through literature review, interview and observation. Furthermore, the system analysis, design and implementation were made using HTML programming, PHP and MySQL database. At the end of the process, system testing was carried out using black box and alpha test. The study results indicate that this new nominative list information system run well and has been useful for BMKG Training and Education Center.